Application of sales forecasting techniques for a company in the home appliances - Akdağ, Tülay (My University, 2019)
Zaman serisi analizi ile tahmin, bir iş ortamında, üretim planlama, satın alma, çizelgeleme ve pazarlama gibi operasyonları etkin ve verimli bir şekilde planlamak için yaygın bir istatistiksel analizdir. Beyaz eşya endüstrisinde, doğru bir satış tahmininin tüm operasyonlarda önemli bir rolü vardır. Bu tezde kullanılan veriler mevsimsel, çevrimsel ve trend modellerine sahip olan dokuz yıllık ve aylık satışları içermektedir. Amaç, soğutma grubu (buzdolabı ve dondurucu) satışlarını zaman serisi tahmin yöntemiyle tahmin ederek şirketin karar verme sürecine yardımcı olmaktır. Autoregressive integrated moving average (ARIMA) ve Nonlinear Autoregressive (NAR) Neural Network tahminleme metotları kullanılmıştır. Analizler için R, R Studio ve MATLAB kullanılmıştır. Zaman serileri, öğrenme seti (ilk 96 ay) ve test seti (son 12 ay) olarak iki gruba ayrılmıştır. Öğrenme seti, ARIMA modellerinin ve NAR ağının uydurulması için kullanılırken, test set tahmin doğruluğunu değerlendirmek için kullanılmıştır. ARIMA modelini zaman serilerine uygulayabilmek için sırasıyla Box-Cox transformasyon ve farkalma kullanılmıştır. Aynı verilere Levenberg-Marquardt geri yayılım öğrenme algoritmasına göre NAR ağı uygulanmıştır. Tahmin edilen değerler gerçek değerlerle, tahmini doğruluk ölçülerine dayalı olarak karşılaştırılmıştır. Seçilen ARIMA modelinin beyaz eşya endüstrisindeki şirketin soğutma grubu satışlarını tahmin etmede güvenilir sonuçlar verdiği görülmüştür.

Prediction through time series analysis is a common statistical task in a business environment for planning operations effectively and efficiently such as production planning, purchasing, scheduling and marketing. In white goods industry an accurate sales forecasting has a significant role in whole operation as well. The data used in this thesis include nine-year monthly sales which have seasonal, cyclical and trend patterns. The objective is to help decision making process of the company by forecasting its cooling group (refrigerator and freezer) sales by a time series forecasting method. Autoregressive integrated moving average (ARIMA) and the Nonlinear Autoregressive (NAR) Neural Network methods have been chosen to use. R software, R Studio and MATLAB have been used for the analyses. The time series have been divided into two subsets as training set (first 96 months) and test set (last 12 months). The training set is used to fit ARIMA model and NAR network, whereas the test set is used to evaluate forecast ability of the model. For applying ARIMA model, in order to obtain stationary data series in the variance and in the mean, Box-Cox transformation and differencing have been applied, respectively. The NAR network based on Levenberg-Marquardt Backpropagation training algorithm has been applied to the same data and comparisons have been done. The forecasted values have been compared with actual values based on the measures of forecast accuracy. It is concluded that the chosen ARIMA model gave reliable results for forecasting the sales of cooling group of company in the white goods industry.
Keywords: Beyaz Eşya Time Series Analysis; Endüstri mühendisliği; Forecasting; Industrial engineering; Tahminleme; White Goods; Zaman Serisi Analizi